Development of Corona-virus-disease-19 Vaccines - Hasegawa, Hideki (JMA Journal, 2021)
The year 2020 opened with news of an epidemic of pneumonia caused by a new coronavirus similar to the SARS coronavirus in Wuhan, China, and subsequently caused a worldwide pandemic. In Japan, the first infected person was found in January, and later, more than 700 passengers and crew members of the Diamond Princess, a large cruise ship that called at Yokohama port, were found to be infected, and the ship was forced to respond to the outbreak. The causative virus was quickly identified as a beta coronavirus similar to the severe acute respiratory syndrome (SARS) coronavirus of 2003 and was named SARS coronavirus 2 (SARS-CoV-2). The disease was named COVID-19. SARS-CoV-2, like SARS-CoV and MERS-CoV, infects the epithelial cells of the lungs and causes viral pneumonia. As of March 7, 2021, more than 116 million people have been infected and more than 2.5 million people have died worldwide. As a result of the global pandemic, regional blockades have been imposed around the world, and the development of vaccines and therapeutic agents has become an urgent necessity in order to restore normal social activities. In this review, the experience of the development of SARS-CoV-2 vaccine is described.